Dosen dan Pertumbuhan Ilmu Pengetahuan - Dominikus Tulasi (Bina Nusantara University, 2013)
The primary purpose of this research is to know lecturers’ activities as the agent of science growth through scientific research and how they highlight a phenomenon using deductive apriory perspective and inductive aposteriory perspective. Deductive apriory perspective is a way to prove an empirical data referring to general propositions that is certain relevant theories with a unit analysis and research object. Whereas, inductive aposteriory perspective is the way oppose to deductive apriory, namely, proving in advance the empirical data on the spot, then followed by creating concepts and propositions which estuary on forming and formulating theory. In other words, deductive and inductive perspective is the binary opposition. Doing research using deductive way is the positivistic aprovident with quantitative approach generating singular truth. Doing research inductively refers to post-positivistic aprovident with qualitative approach affecting on multifaced truth. Research method used in this study is the inductive-explorative-qualitative approach, a case study using communication semiotics analysis, estuary at researcher’s internalization toward the phenomenon of lecturers’ scientific activities of Economics and Communication Faculty at Binus University. Result obtained of this study is to reconstruct researcher’s comprehension of lecturers’ scientific research accumulated in appropriate concepts and propositions using deductive-quantitative and inductive-qualitative approach in its implementation on scientific research of Economics and Communication Faculty lecturers at Binus University. Based on the result it can be concluded that applying scientific research activities of lecturers’ holistic understanding toward deductive apriory and inductive apsoteriory will generate satisfied result of a research. Improving and intensifying a phenomenon by implementing quantitative and qualitative methods rightfully, following scientific rules, will affect scientific values as expected. Whereas, in some cases, lecturers apply mixed method using quantitative and qualitative approach simultaneously in studying a phenomenon.